(untitled) (Physical Education, Health and Social Sciences, 2024)
Health related fitness is a blessing.it is the quality which enables a person to perform the daily routine tasks efficiently and effectively. Overweight is one of the factors that affect the health-related fitness. The main aim of the current study was to determine the comparative effects of hatha yoga training and aerobic training upon circumference of neck, chest and waist among overweight college students. Two groups each of twenty-five subjects were selected for the study through PAR-Q having age 20 to 24 years. The pretest data on dependent variables was collected through tape measurement. Ten weeks treatment each of Hatha yoga and aerobic training was given to the subjects of hatha group and aerobic group respectively for three days on alternate days per week. After the treatment, posttest data was collected of dependent variables through the procedure as adopted for the pretest data. The collected data (pre and post) of the subjects of each group was tabulated. Mean, standard deviation, paired sample t test and independent sample t test were used to analyses the data. The significance level was fixed at 0.05. it was concluded that both trainings have significant effects on the circumference of neck, chest and waist. Besides it, aerobic exercises of 10 weeks had better effects on the circumference of chest and waist compared to hatha yoga while hatha yoga have better effects on neck among overweight college students of 20 to 24 years of age. it is recommended that overweight students should take part in the hatha yoga exercises and aerobic exercises for the enhancement of their health-related fitness. Key words: HathaYoga, Aerobic, neck, chest, waist, overweight